Nanoscale silician defects in magnetite record protolith inheritance and control chain silicate growth during skarn formation - Jing Xu; Yuri Tatiana Campo-Rodriguez; Cristiana L. Ciobanu; Nigel J. Cook; Ashley Slattery; Benjamin P. Wade; Jiaxing Hu; Taiping Zhao (Lithos, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Indium mineralization in the world-class Dachang Sn-polymetallic district, Southwest China - Jing Xu; Nigel J. Cook; Cristiana L. Ciobanu; Taiping Zhao; Jiadai Li; Qiaoqiao Zhu; Wen Jiang (Mineralium Deposita, 2026)

Timing of meteoric-water incursion controls the scale of tin mineralization - Peng Liu; Bernd Lehmann; Francois Holtz; Stefan Weyer; Nigel J. Cook; Maria Rosa Scicchitano; Christopher L. Kirkland; Xiaoyan Li; Zhian Bao; Zexian Cui; Franziska D.H. Wilke; Honglin Yuan; et al. (Geochimica et Cosmochimica Acta, 2025)

The state and fate of noble metals in bornite and digenite - Samuel A. King; Cristiana L. Ciobanu; Nigel J. Cook; Ashley D. Slattery; Sarah E. Gilbert; J. Richard Kyle; Kathy Ehrig; Jie Yao (Lithos, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Trace element distributions among Cu-(Fe)-sulfides from the Olympic Dam Cu-U-Au-Ag deposit, South Australia - Samuel A. King; Nigel J. Cook; Cristiana L. Ciobanu; Kathy Ehrig; Sarah Gilbert; Benjamin Wade; Yuri T. Campo Rodriguez (Mineralium Deposita, 2025)

Coupled Lu-Hf and U-Pb apatite geochronology of Jatobá orebody supports ∼ 2.5 Ga metamorphism in deep shear zones from southern Copper Belt, Carajás Domain, Brazil - Yuri Tatiana Campo-Rodriguez; Cristiana L. Ciobanu; Sarah Gilbert; Benjamin Wade; Nigel J. Cook; Maria Emilia Schutesky; Kathy Ehrig (Precambrian Research, 2025)

Monazite, lanthanide-rich glasses, and other trace elements in copper smelter slags: constraints on critical metal behaviour in Si-Fe-rich melts - Hassan Gezzaz; Cristiana L. Ciobanu; Nigel J. Cook; Kathy Ehrig; Ashley Slattery; Benjamin Wade; Sarah Gilbert; Yuri T. Campo Rodriguez (Mineralogy and Petrology, 2025)
Furnace slags are potential new sources of critical metals. We undertook a micron- to nanoscale study that addresses speciation, distribution and associations of phases in air-cooled flash furnace (FF, oxidised) and electric furnace (EF, reduced) slags from the Olympic Dam mining-smelting-refinery operation. Results enable understanding of the behaviour and partitioning of critical metals between melt and cooling crystalline phases in a controlled smelter environment that mimics Fe-Si-rich systems in Nature. Melts at ~ 1300 °C result in slags that differ in the relative proportions of component phases. Both FF and EF slags comprise major magnetite and two, compositionally distinct Si-Fe-rich glasses (glass-1 and -2); fayalite is a main component of EF slag. Glass-1 is rich in REE + Y (4.5–5.4 wt%, Ce 2 O 3 + La 2 O 3 ) and contains dendritic monazite-(Ce). Glass-2 (~ 70 wt% SiO 2 ) contains < 1 wt% Ce 2 O 3 + La 2 O 3 . The EF slag reaction sequence is: magnetite $$→$$ → fayalite + glass-1 $$→$$ → monazite $$→$$ → glass-2. Immiscibility of REE-rich liquid from Si-Fe-rich melt is inferred from amorphous ‘monazite-like’ droplets. Chondrite-normalised fractionation patterns are defined by downwards-sloping LREE segments in both glasses. Partition coefficients are calculated for magnetite and fayalite relative to glasses. D REY for HREE exceeds those for LREE in all phases and fayalite has an order of magnetite higher D HREE than co-existing EF magnetite. Applying lattice strain models to experimental values show excellent fits for D HREE-model trends, even if lattice strain is not the sole factor controlling partitioning. Melt polymerisation, variable/unpredictable oxidation states, and constraints from specific crystallographic sites, also impact on observed trends. This study provides clues to element behaviour in metallurgical plants that can assist potential utilization of copper smelter slags to meet the demand for REE and other contained critical metals.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Mineralogy, mineral chemistry, and genesis of Cu-Ni-As-rich ores at Lisheen, Ireland - Max Frenzel; Markus Röhner; Nigel J. Cook; Sarah Gilbert; Cristiana L. Ciobanu; John F. Güven (Mineralium Deposita, 2025)
The Irish Orefield is characterised by the presence of both Zn-Pb- and Cu-Ni-As-rich deposits, prospects, and orebodies in similar structural and stratigraphic positions. However, the genetic relationships between these mineralisation types are still debated. In this article, we present new mineralogical, paragenetic, and mineral-chemical observations from the Cu-Ni-As-rich ores at the classic Lisheen deposit, County Tipperary. These observations indicate the intimate association and cogenetic nature of these ores with the more abundant Zn-Pb-rich mineralisation. Specifically, both mineralisation types appear to have formed at the same time, under similar physicochemical conditions, and from the same ore fluids. In addition, both types of mineralisation contain elevated Ge contents. The cogenetic nature of the two mineralisation types, the relative absence of Cu-Ni-As-rich ores from most of the larger Irish-type Zn-Pb deposits compared to expectations derived from probable ore fluid compositions, and finally, the known geological characteristics of larger Cu-Ni-As-rich ore bodies, like Gortdrum, indicate that significant Cu-Ni-As-rich mineralisation could be present at lower stratigraphic levels across the Irish Orefield. Areas with extensive known Zn-Pb mineralisation are expected to be particularly prospective for such ores, which may occur at stratigraphic levels as deep as the Old Red Sandstone. This may have additional implications beyond Ireland, and could point to the potential for undiscovered Cu-rich ores in low-temperature carbonate-hosted Zn-Pb districts elsewhere.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Redefining timing, genesis and geodynamic setting of polymetallic skarn mineralization, Gangdese belt, Tibet, from LA–ICP–MS garnet U–Pb geochronology - Jing Xu; Jiadai Li; Nigel J. Cook; Cristiana L. Ciobanu; Shitou Wu; Benjamin P. Wade; Taiping Zhao; Liyuan Wang (Gondwana Research, 2024)

Trace element impurities in anode copper from Olympic Dam, South Australia - Nigel J. Cook; Kathy Ehrig; Cristiana L. Ciobanu; Sarah E. Gilbert; Hassan Gezzaz (Minerals Engineering, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Detailed characterisation of precious metals and critical elements in anode slimes from the Olympic Dam copper refinery, South Australia - Nigel J. Cook; Kathy Ehrig; Cristiana L. Ciobanu; Samuel A. King; Vanessa Liebezeit; Ashley D. Slattery (Minerals Engineering, 2024)

Implications for metallogenic evolution of the giant Zhenyuan gold deposit (Yunnan, SW China) from textures and geochemical compositions of pyrite - Huichao Zhang; Nigel J. Cook; Hongrui Zhang; Zengqian Hou; Peng Chai; Wei Li; Sarah Gilbert (Contributions to Mineralogy and Petrology, 2024)

Pb-bearing Cu-(Fe)-sulfides: Evidence for continuous hydrothermal activity in the northern Olympic Cu-Au Province, South Australia - Nicholas D. Owen; Nigel J. Cook; Rahul Ram; Joël Brugger; Roland Maas; Danielle S. Schmandt; Cristiana L. Ciobanu (Precambrian Research, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Mafic mineral clots and microgranular enclaves in A-type Hiltaba Suite granites from the Gawler Craton, South Australia: Origins and implications - Alkiviadis Kontonikas-Charos; Kathy Ehrig; Nigel J. Cook; Cristiana L. Ciobanu (Lithos, 2023)

Fingerprinting involvement of evaporites in magmatic-hydrothermal processes from the Jinshandian Fe skarn deposit, eastern China, using apatite geochemistry - Qiaoqiao Zhu; Guiqing Xie; Nigel J. Cook; Cristiana L. Ciobanu (Lithos, 2023)

Skarn-style alteration in Proterozoic metasedimentary protoliths hosting IOCG mineralization: the Island Dam Prospect, South Australia - William Keyser; Cristiana L. Ciobanu; Kathy Ehrig; Marija Dmitrijeva; Benjamin P. Wade; Liam Courtney-Davies; Max Verdugo-Ihl; Nigel J. Cook (Mineralium Deposita, 2022)
New mineralogical, geochemical, and geochronological data are presented for the Island Dam prospect, Olympic Cu-Au Province, South Australia. Skarn assemblages comprising actinolite/phlogopite + K-feldspar + magnetite suggest the presence of calcareous protoliths at Island Dam and indicate high-temperature alkali-calcic alteration in the early stages of IOCG mineralization, as seen in other deposits in the region. Dating of lamellar hematite intergrown with Cu-Fe-sulfides allows the timing of the alteration-mineralization event to be constrained at 1594 ± 28 Ma, contemporaneous with the ~ 1.59 Ga IOCG mineralization event recorded across the eastern Gawler Craton. The host metasedimentary sequence can be correlated to the Wallaroo Group based on lithology and fabrics, and stratigraphically by an underlying ~ 1850 Ma Donington Suite granite and the new U–Pb ages for superimposed mineralization. Oscillatory zoned silician magnetite in skarn displays a trace element signature comparable to that observed in the outer shell of the Olympic Dam deposit and the nearby Wirrda Well prospect and is consistent with early stages of IOCG mineralization. The geochemical signatures of hematite from skarn and banded Fe-rich metasedimentary rocks share a common enrichment in W, Sn, Mo, Th, and U seen in hematite from IOCG-style mineralization across the Gawler Craton. Relative enrichment in As, Sb, Ni, and Co is, however, specific to iron-oxides from banded Fe-rich metasedimentary rocks. These features can be attributed to pre-existing iron-rich lithologies.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Evolution of a hydrothermal ore-forming system recorded by sulfide mineral chemistry: a case study from the Plaka Pb–Zn–Ag Deposit, Lavrion, Greece - Max Frenzel; Panagiotis Voudouris; Nigel J. Cook; Cristiana L. Ciobanu; Sarah Gilbert; Benjamin P. Wade (Mineralium Deposita, 2022)
Laser ablation-inductively coupled plasma-mass spectrometry and electron-probe microanalysis were used to investigate the trace-element contents of sphalerite, chalcopyrite and pyrite from the Plaka Pb–Zn–Ag deposit. Using petrographic observations, the analytical results could be linked to the temporal evolution of the Plaka ore-forming system. Sphalerite chemistry reliably records the temperature and f S 2 evolution of the system, with estimated formation temperatures reproducing the microthermometric results from previous fluid-inclusion studies. Chalcopyrite chemistry also shows systematic variations over time, particularly for Cd, Co, Ge, In, Sn and Zn concentrations. Measurable pyrite was only found in association with early high-temperature mineralisation, and no clear trends could therefore be identified. We note, however, that As and Se contents in pyrite are consistent with formation temperatures estimated from co-existing sphalerite. Statistical analysis of the sphalerite data allowed us to identify the dominant geological controls on its trace-element content. The three investigated factors temperature, f S 2 , and sample location account for > 80% of the observed variance in Mn, Fe, Co, Ga, Ge, In, Sb and Hg concentrations, and > 60% of the observed variance in Cd and Sn concentrations. Only for Cu and Ag concentrations is the explained variance < 50%. A similarly detailed analysis was not possible for chalcopyrite and pyrite. Nevertheless, comparison of the results for all three investigated minerals indicates that there are some systematic variations across the deposit which may be explained by local differences in fluid composition.

Intracrystalline migration of polymetallic Au-rich melts in multistage hydrothermal systems: example from the Xiaoqinling lode gold district, central China - Wei Jian; Jingwen Mao; Nigel J. Cook; Lei Chen; Guiqing Xie; Jiandong Xu; Shiwei Song; Jialong Hao; Ruiying Li; Junchen Liu (Mineralium Deposita, 2022)

Indium distribution in sphalerite from sulfide–oxide–silicate skarn assemblages: a case study of the Dulong Zn–Sn–In deposit, Southwest China - Jing Xu; Nigel J. Cook; Cristiana L. Ciobanu; Xiaofeng Li; Alkiviadis Kontonikas-Charos; Sarah Gilbert; Youhu Lv (Mineralium Deposita, 2021)

Numerical modelling of rare earth element fractionation trends in garnet: a tool to monitor skarn evolution - Jing Xu; Cristiana L. Ciobanu; Nigel J. Cook; Youye Zheng; Xiaofeng Li; Benjamin P. Wade; Max R. Verdugo-Ihl; Wenyuan Gao; Qiaoqiao Zhu (Contributions to Mineralogy and Petrology, 2020)

Defining early stages of IOCG systems: evidence from iron oxides in the outer shell of the Olympic Dam deposit, South Australia - Max R. Verdugo-Ihl; Cristiana L. Ciobanu; Nigel J. Cook; Kathy J. Ehrig; Liam Courtney-Davies (Mineralium Deposita, 2020)

Crystal chemistry of titanite from the Roxby Downs Granite, South Australia: insights into petrogenesis, subsolidus evolution and hydrothermal alteration - Alkiviadis Kontonikas-Charos; Kathy Ehrig; Nigel J. Cook; Cristiana L. Ciobanu (Contributions to Mineralogy and Petrology, 2019)

Textures and trace element signatures of pyrite and arsenopyrite from the Gutaishan Au–Sb deposit, South China - Wei Li; Nigel J. Cook; Gui-Qing Xie; Jing-Wen Mao; Cristiana L. Ciobanu; Jian-Wei Li; Zhi-Yuan Zhang (Mineralium Deposita, 2019)

Mineralogical, textural, sulfur and lead isotope constraints on the origin of Ag-Pb-Zn mineralization at Bianjiadayuan, Inner Mongolia, NE China - Degao Zhai; Jiajun Liu; Nigel J. Cook; Xilong Wang; Yongqiang Yang; Anli Zhang; Yingchun Jiao (Mineralium Deposita, 2019)

Discrimination and Variance Structure of Trace Element Signatures in Fe-Oxides: A Case Study of BIF-Mineralisation from the Middleback Ranges, South Australia - Marija Dmitrijeva; Andrew V. Metcalfe; Cristiana L. Ciobanu; Nigel J. Cook; Max Frenzel; William M. Keyser; Geoff Johnson; Kathy Ehrig (Mathematical Geosciences, 2018)

Rare earth element geochemistry of feldspars: examples from Fe-oxide Cu-Au systems in the Olympic Cu-Au Province, South Australia - Alkis Kontonikas-Charos; Cristiana L. Ciobanu; Nigel J. Cook; Kathy Ehrig; Sasha Krneta; Vadim S. Kamenetsky (Mineralogy and Petrology, 2018)

Postmagmatic magnetite–apatite assemblage in mafic intrusions: a case study of dolerite at Olympic Dam, South Australia - Olga B. Apukhtina; Vadim S. Kamenetsky; Kathy Ehrig; Maya B. Kamenetsky; Jocelyn McPhie; Roland Maas; Sebastien Meffre; Karsten Goemann; Thomas Rodemann; Nigel J. Cook; Cristiana L. Ciobanu (Contributions to Mineralogy and Petrology, 2016)

Trace and minor elements in sphalerite from metamorphosed sulphide deposits - Julian A. Lockington; Nigel J. Cook; Cristiana L. Ciobanu (Mineralogy and Petrology, 2014)

Multivariate Analysis of an LA-ICP-MS Trace Element Dataset for Pyrite - Lyron Winderbaum; Cristiana L. Ciobanu; Nigel J. Cook; Matthew Paul; Andrew Metcalfe; Sarah Gilbert (Mathematical Geosciences, 2012)

The Niujiaotang Cd-rich zinc deposit, Duyun, Guizhou province, southwest China: ore genesis and mechanisms of cadmium concentration - Lin Ye; Nigel J. Cook; Tiegeng Liu; Cristiana L. Ciobanu; Wei Gao; Yulong Yang (Mineralium Deposita, 2012)

Observed relationships between El Niño‐Southern Oscillation, rainfall variability and vegetation and fire history on Halmahera, Maluku, Indonesia - SANDER VAN DER KAARS; NIGEL TAPPER; ELLYN J. COOK (Global Change Biology, 2010)
A temporally high‐resolution palynological study of the uppermost section of core MD98‐2180 from Kau Bay, Halmahera, Indonesia, provides a vegetation and fire record covering the last 250 years. The record is compared with the Maluku Rainfall Index, Southern Oscillation Index (SOI) and southern hemisphere winter sea surface temperatures (SST) for the central Pacific Ocean based on instrumental data, as well as reconstructions of the SOI and the central Pacific SST and historically recorded El Niño events. The results show that significant El Niño events are generally associated with increased representation of Dipterocarpaceae pollen, probably reflecting the mass‐flowering of this taxon during El Niño‐Southern Oscillation (ENSO) droughts, and elevated charcoal levels, reflecting a greater incidence of fires during these extremely dry periods, while humid phases show increased fern numbers. Our findings demonstrate that pollen records ‘ecological’ in scale can provide useful additional proxy records of ENSO events.

Textural variation in the pyrite-rich ore deposits of the Røros district, Trondheim Region, Norway: implications for pyrite deformation mechanisms - Craig D. Barrie; Nigel J. Cook; Alan P. Boyle (Mineralium Deposita, 2010)

Regional setting and geochronology of the Late Cretaceous Banatitic Magmatic and Metallogenetic Belt - Cristiana L. Ciobanu; Nigel J. Cook; Holly Stein (Mineralium Deposita, 2002)